A Phenomenological Study of Identification Process in Male patients of a Referral Center with Abnormal Sexual Orientations (Homosexual) and Their Challenges - Jebeli, Seyed Jalil; Hajhosseini, Mansoureh; Madani, Yaser; Ahmadi, Sedigheh (Archives of Men’s Health, 2023)
Introduction: The purpose of this research was to explain the identification process in young homosexual men. Material & Methods: The method of this study was phenomenological. The data was categorized and processed based on Strauss and Glaser’s interpretive analysis approach. In this research, participants were selected with a purposeful sampling method. Finally, a semi-structured interview was conducted with 15 referred homosexual men with a mean age of 23.9. Result: results were classified into two aspects of the identification process, and challenges/risks. The process of identity formation in young homosexual men included three steps: a. childhood exploration, b. adolescent confusion and identity crisis, and c. youth encounter and acceptance. Also based on the challenges and risks, the experience of negative emotions, such as feeling frustrated, anxiety, guilt, and depression were achieved in the emotional dimension. Conclusion: Iranian homosexual men pass difficult periods to seek identity. And finally, they may not achieve a complete identity, their challenges include: 1) a. becoming sensitive and feeling differently from others, b. realizing his orientation, c. suffering a great deal of religious conscience and selflessness, d. starting to change orientation without success, e. accepting identity desperately. 2) a. realizing they cannot reveal gay identity in family and society, b. having to put on a mask and play a role, c. facing individual and social challenges and due to these tensions, d. facing emotional and behavioural challenges, e. referring to counsellors for getting help and finding his real and correct identity.